Immobilization of cyclodextrin glucanotransferase on electrospun polyvinyl alcohol nanofibers - Saallah, Suryani (2014)
There are many types of nanostructured materials that have been used for enzyme immobilization which include nanoporous, nanoparticles and nanofibers. The use of nanofibers as support material is favorable owing to their high porosity and interconnectivity and can be easily recovered and reuse. In this study, cyclodextrin glucanotransferase (CGTase) enzyme was successfully immobilised on PVA nanofibers via post-spinning and simultaneous electrospraying and electrospinning. In the post-spinning method, the PVA solution was electrospun to produce nanofibrous membrane at first and followed by the electrospraying of CGTase particles onto the membrane. The latter method involved the simultaneous electrospraying of CGTase solution and electrospinning of PVA solution conducted at opposite polarity. Before the immobilisation step, the transformation of CGTase from solution to solid particles via electrospraying in Taylor cone-jet mode was studied to obtain fine and monodispersed particles that can be attached uniformly on the PVA membrane. The CGTase functional groups and activity were preserved during the process as confirmed by FTIR and enzyme activity analysis. The Columbic fission that occurred during electrospraying has changed the enzyme morphology from clusters into a single particle as observed by Scanning Electron Microscope (SEM) and effectively reduced the average enzyme particle size from 200 ± 117 nm to 75 ± 34 nm when the spraying tip to the collector distance was increased from 10 cm to 25 cm. The enzyme particles collected at the longest distance demonstrated the highest enzyme activity. The microstructure of electrosprayed CGTase immobilised on PVA nanofibers was observed using SEM and the effectiveness of the two immobilisation approaches was compared in terms of enzyme loading, enzyme activity and reusability with enzyme concentration ranging from 1 to 7.5% v/v. Post-spinning deposition produced nanofibers with denser particles deposited on its surface, while uniform distribution of particles within the nanofibers was observed when simultaneous electrospraying and electrospinning was applied. Higher enzyme loading efficiency was obtained by using the simultaneous method with maximum value of 14 mg/g compared to 9 mg/g for the post-spinning method. The enzyme activity analysis showed that up to 17% higher enzyme activity could be achieved through the simultaneous method in comparison to the post-spinning. Vapour phase crosslinking that was applied to the CGTase/PVA membranes to facilitate the enzyme reusability did not cause significant losses to the immobilised enzyme activity. The membranes produced via both the post-spinning and simultaneous method exhibited almost similar trend of reusability with up to 50% of the initial enzyme activity retained after the fifth cycle of the enzymatic reaction. The results indicate that the electrospraying and and electrospinning hybrid method is a promising approach for enzyme immobilisation.